Thinking Fast and Slow by Daniel Kahneman - Dineen, Tana (Journal of Scientific Exploration, 2014)
Passing through an airport recently, I happened to notice Thinking Fast and Slow on a rack in the bookstore, alongside The Racketeer by John Grisham, Inferno by Dan Brown, and Fifty Shades of Grey by E. L. James. Having read Kahneman’s book, I knew that it lacked the sex, action, and pop appeal that these other books offered, but that what it was short of in these characteristics it made up for in depth and revelation, offering an unfamiliar form of intrigue—something personal rather than scandalous—altogether riveting. Since its first release in 2011, Thinking Fast and Slow has received an overwhelming number of glowing reviews. One pronounces Kahneman “the world’s greatest living psychologist;” others describe the book as “one of the greatest and most engaging collections of insights into the human mind” and “a masterpiece.” While these are well-deserved accolades, what earned Kahneman the Nobel Prize in economics and has gotten his book onto the rack of popular best-sellers isn’t just the theories or the research but rather the surprise and self-reflection his pulling together of this amazing body of knowledge evokes.